INFECTIOUS FEVER-CROSS SECTIONAL STUDY OF 500 PATIENTS - DR.V.PADMA; DR.SYED MOHAMMED JAVID M.S.A. (International Journal of Pharma and Bio Sciences, 2014)
Infections are one of the leading causes of morbidity and mortality in our country. This study was undertaken to evaluate the changing profile in patients presenting with infectious fevers. To study the clinical profile like age, sex, fever duration and associated systemic symptoms in patients with infectious fever. To study the most common cause of infectious fever. To study the various organ dysfunction and the causes of organ dysfunction in patients with infectious fever. 500 patients with fever were analysed, 54% were males and 46 %were females. The common causes of infectious fever were dengue fever(22%), malaria (24%), leptospirosis (22%), enteric fever (12%) , urinary tract infection(8%), chikungunya, (6%)tuberculosis,(3%)pneumonia (2%), and pyrexia of unknown origin(1%).Common complications of malaria were cerebral malaria (2%),jaundice (10.%) and renal failure (1%).Anicteric hepatitis (81%) was the most common presentation of leptospirosis and renal failure occurred in 2% of the cases .Among patients with dengue fever 1% had dengue encephalopathy,1% had post dengue psychosis and 3%had pancreatitis. Malaria, leptospirosis, dengue fever and enteric fever were the common causes of infectious fevers in this study. Early diagnosis and treatment has reduced morbidity and mortality in fever patients.